Collegial Leadership and Election in Muhammadiyah: Institutional Ways to Diffuse the Religious Authority of Leaders - Kim, Hyung-Jun (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2023)
Muhammadiyah advocates for the equal and rational standing of Muslims, underscoring that judgment lies solely with Allah and discouraging hierarchical leadership privileges. This viewpoint permeates its organizational structure, portraying leaders as dedicated members without elevated status. Alongside its emphasis on egalitarianism and rationality, Muhammadiyah has developed organizational mechanisms, aimed at preventing the concentration of religious authority in the hands of popular leaders. The article explores two of these mechanisms, collegial leadership and elections. Collegial leadership establishes a collective oversight body, ensuring equal rights for each leader. The unique election system, requiring the choice of thirteen candidates, prevents individual dominance and a potential landslide victory. By minimizing differences, emphasizing similarities, and discouraging the showcasing of individual merits and popularity, these mechanisms effectively diffuse religious authority within Muhammadiyah’s leadership.